Zarządzanie wiedzą w korporacjach transnarodowych - przypadek Hewlett-Packard - Simpson, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Knowledge management, as a new domain, is not explained by too many theoretical models,which could be used in practise. Consulting firms use in practise two kind of strategy: codificationand personalization. The article shows that in the analyzed corporation you can find both of them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 336-344